All-Dielectric Meta-lens Designed for Photoconductive Terahertz Antennas - Qing Yu; Jianqiang Gu; Quanlong Yang; Ying Zhang; Yanfeng Li; Zhen Tian; Chunmei Ouyang; Jiaguang Han; John F. OHara; Weili Zhang (IEEE Photonics Journal)
We present an all-dielectric meta-lens designed to collimate terahertz waves emitted from a terahertz antenna. The meta-lens is not only thinner than a conventional bulk silicon lens, but also promises to eliminate the use of parabolic mirrors in a terahertz time-domain spectroscopy system. A systematic numerical study reveals that the meta-lens exhibits excellent performance in both the emitter and detector modules, converting between the spherical wave of the antennas and the collimated beam. The frequency and alignment dependences of the meta-lens are also investigated to comprehensively map its response characteristics. The all-dielectric meta-lens presented here may pave a way in developing high-performance integrated photoconductive terahertz antenna components.